Patient Safety Concept and Implementation in Traditional/Complementary Alternative Medicine (TM/CAM) - Amalia, Anindini Winda; Purba , Yunita Sari; Husen, Husen; Sahuri , Sahuri; Arjuni , Defi; Rosyita , Hafna (Syntax Corporation Indonesia, 2024)
Safety patient in-service health felt important for increasing the quality of service health. Development of TM/CAM services in Indonesia starts to take place with the existence of Law No. 17 of 2023. However, in practice is not yet lots done because it still does not have a receptacle or service. Besides that still limited availability of TM/CAM staff with formal education, Done with studies literature about concept safety patients and implementation in the TM/CAM services. A literature review is a series of related research with library data collection methods, or object research his research dug through a diverse information article journal / bibliography.. Analysis of the data used in the study using an analysis of which one is a concept and which the other is an implementation in the TM/CAM Thereby important implementation of the patient safety concept in a way general under ICPS developed and how its implementation in TM/CAM . The point similarity description detection, incident, harmful incident is first known with Adverse vent, mitigation, and contributing factors/hazards in TM/CAM. Report risks, incidents, harmful incidents, and their importance to climate and culture safety patients in TM/CAM Some incidents mostly originate from the biological (herbal) and acupuncture is relatively small. With increasing interest of public to safety healthcare TM/CAM professions parts of the world and practitioners individual have responsible to improve safety products and practices .This is by the perception public that TM/CAM is natural and considered safe. Therefore a need exists for reporting and research across the country to get a sufficient amount for analysis forward Various types incident potentially harmful related with TM/CAM, as well various the activities described as TM/CAM practices as well amount organizations involved in training or supervision practitioner . This issues need to be considered in the evaluation strategies for reducing future risks.